Modeling and diffusion of news topics in social media: Features and factors of the emergence of news in a twitter informative channel (2019)
This study aims to characterize the modeling and diffusion of news topics in social media and determine the factors that influenced them. With Big Data analysis methods, such as topic modeling and sentiment analysis, we analyzed one year of tweets from Colombian newspaper El Tiempo. We found that the appearance of long-term topics was related to the message's attributes. Theoretical implications and contributions considering Diffusion of Innovations' model are mentioned. © 2018 Universidad de Guadalajara. All rights reserved.